Quality Management Practices among High Technology Firms: One-way ANOVA Analysis - Mastora Mustafar; Risyawati Mohamed Ismail; Amran Rasli; Salmah Omar (International Journal of Supply Chain Management, 2019)
Quality management practices (QMP) are modern approaches used to enhance firm performance. Although there are numerous research findings on quality management practices, the focus of the research is not much on high technology firms. Hence, this study aims to look at the different levels of quality management practices and firm performance in high technology firms based on firm profiles such as firm cluster, firm size and duration of the operation. Data were collected using questionnaires and analyzed using descriptive and inferential analysis. The one-way ANOVA analysis shows that quality management practices among high technology firms were moderate and the results also indicate that there is insufficient evidence to support the existence of differences based on statistical evidence between QMP and firm cluster, firm size, and duration of the operation. This research finding also allows practitioners to gain a deeper knowledge and understanding of the importance QMP and firm performance in the high technology firms.